A descriptive study of eye and head movements in versive seizures. (May 2022) - Fotedar, Neel; Gajera, Prasannakumar; Pyatka, Nataliya; Nasralla, Salam; Kubota, Takafumi; Vaca, Guadalupe Fernandez-Baca; Shaikh, Aasef G.; Lüders, Hans O.
Abstract: Background: Versive seizures, consisting of forced, involuntary, sustained and unnatural turning of eyes and head toward one side, lateralize to the hemisphere contralateral to the direction of the eye and head turn. The characteristics of eye and head movements in version have been rarely and incompletely studied in spontaneous epileptic seizures as opposed to direct cortical stimulation studies. Methods: We performed a single center retrospective analysis of a cohort of 28 patients with 43 seizures, who had been admitted to the adult epilepsy monitoring unit at University Hospitals Cleveland Medical Center between January 2009 and August 2020. We only included patients with clear, high-resolution seizure videos and interpretable EEG. Results: The eye movements were conjugate and contralateral to the hemisphere of seizure onset in 100% of the focal-onset seizures. The eye movements were saccadic in 89.3% with a predominant vector in oblique upward direction in 86.8% of the seizures. Head deviation was present in 100% of the seizures and the eyes and head deviated in the same direction in 97.6% of the seizures. In addition to deviation along the horizontal meridian, there was a vertical component to the head deviation as well, as evidenced by movement of the chin upward along the vertical axis in 93% of the seizures, thus indicating strong activation of the sternocleidomastoid muscle ipsilateral to the hemisphere of seizure onset. Concomitant facial motor activity ipsilateral to the direction of version was seen in 93% of the seizures. The most common pattern was a clonic superimposed on tonic facial contraction. Discussion: Version remains a reliable and highly lateralizing sign. The majority of the eye movements during version occur in a saccadic fashion rather than one smooth movement, mostly in an oblique upward direction. Head deviation is very closely associated with eye deviation, thus indicating a common symptomatogenic zone for both, which is most likely the frontal eye field. A high concurrence of ipsilateral facial motor activity with version is likely because of close proximity of the frontal eye field to the face area in the primary motor cortex.